Hand gesture based user interface system - Chin, Sui Yee (2013)
This project is to describe about the hand gesture based on user interface that would able to replace mouse. In this project, we would focus to new system which we will use own hand to replace mouse and control the mouse pointer to do all mouse tasks in the computer via webcam. We would discuss about what advantages of system among existing system through several ways and more convenient than usual system. The technology that used is related in using Webcam and Opencv libraries. I have been using Rapid Application Development (RAD) in developing my project. There are four phases in this model: Requirement Planning, User Design, Construction Phase, and Cutover Phase. Rapid Application Development is slightly different from the Systems development life cycle (SDLC). The Rapid Application Development is focus more on implementation and construction but less on design and documentation. Last but not least, I have arranged a time schedule to help me in developing the project so that I would be able to finish my project in time.